Differentiating vacuum-assisted breast biopsy from core needle biopsy: Is it necessary? - Nakano, Satoko (Br J Radiol, 2018)
Needle biopsy has replaced excisional biopsy as a definitive diagnostic technique for breast tumours, although excisional biopsy is still used for complete tumour removal for therapeutic and/or diagnostic purposes. Many vacuum-assisted breast biopsy (VAB) systems have been made available by several manufacturers since the release of the Mammotome (MMT) by Johnson & Johnson in 1995. Several recent discussions have been conducted to identify whether core needle biopsy (CNB) or VAB, is more appropriate. However, currently available VAB systems differ from the conventional system (i.e. articulate arm type 11-gauge(G) MMT), and the characteristics of both CNB and VAB have been improved. In CNB, a 14-G needle is frequently used to obtain a larger sample. By contrast, VAB is considered easier to perform because it uses a thinner needle and a lighter, non-tethered system. When differentiating CNB from VAB, the type of VAB should also be defined. In this review, we discuss the characteristics of ultrasonography-guided VAB and CNB with a focus on practical issues such as the number of samples and volume of tissue obtained during ultrasonography-guided needle biopsy.